Cost-effectiveness of quadrivalent versus trivalent influenza vaccine for elderly population in China. Issue 5 (29th January 2020) - Jiang, Minghuan; Li, Pengchao; Wang, Weihua; Zhao, Mingyue; Atif, Naveel; Zhu, Shan; Fang, Yu
Abstract: Background: Influenza-associated excess death occurred most in the elderly. We aimed to assess the cost-effectiveness of quadrivalent influenza vaccine (QIV) versus trivalent influenza vaccine (TIV) for prevention of influenza infection among elderly population in China. Methods: A decision-analytic model was developed to compare 1-year clinical and economic outcomes of three influenza vaccination options (no vaccination, TIV, and QIV) in a hypothetical cohort of Chinese elderly aged 69 years. Outcome measures included cost, influenza infection rate, influenza-related mortality rate, quality-adjusted life-years (QALY) loss, and incremental cost-effectiveness ratio (ICER) from societal perspective. Sensitivity analyses were performed to examine the uncertainty of model inputs. Results: Base-case results showed no vaccination was dominated (more costly at higher QALY loss) by TIV and QIV. QIV was more costly (USD56.29 versus USD54.28) with lower influenza infection rate (0.608 versus 0.623), mortality rate (0.00199 versus 0.00204), and QALY loss (0.01213 versus 0.01243) than TIV. QIV was cost-effective compared to TIV with ICER of 6, 700 USD/QALY below the willingness-to-pay threshold (29, 580 USD/QALY). One-way sensitivity analysis found the cost-effectiveness of QIV was subject to the relative risk of vaccine effectiveness of QIV versus TIV, and TIV would be cost-effective if the relative risk was below 1.05. In 10, 000 Monte Carlo simulations, the probabilities of QIV, TIV, and no vaccination to be cost-effective were 86.3%, 13.7%, and 0%, respectively. Conclusion: QIV appears to be a cost-effective option compared to TIV and no influenza vaccination for elderly population in China.